2020
DOI: 10.1002/ejoc.202001118
|View full text |Cite
|
Sign up to set email alerts
|

Selective Debromination of α,α,α‐Tribromomethylketones with HBr–H2O Reductive Catalytic System

Abstract: A debromination of α,α,α‐tribromomethylketones is developed for chemoselective synthesis of α‐mono‐ and α,α‐dibromomethylketones with high selectivity under H2O–HBr reductive conditions. This method offers an efficient and direct way to synthesize α‐mono or α,α‐dibromomethylketone compounds in high to excellent yields through the process of HBr self‐circulation in water.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0
2

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 20 publications
0
3
0
2
Order By: Relevance
“…We then sought to develop a kinetic model which would fit the data collected and incorporate our experimental observations. Based on Figure 4D, we built the model to include the formation of 9 a under equilibrium, which is a previously ‐unreported feature of the haloform reaction [45] . A rate constant for the decay of acetophenone 1 a was experimentally determined and then locked into the model, enabling others to vary from it.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…We then sought to develop a kinetic model which would fit the data collected and incorporate our experimental observations. Based on Figure 4D, we built the model to include the formation of 9 a under equilibrium, which is a previously ‐unreported feature of the haloform reaction [45] . A rate constant for the decay of acetophenone 1 a was experimentally determined and then locked into the model, enabling others to vary from it.…”
Section: Figurementioning
confidence: 99%
“…Based on Figure 4D, we built the model to include the formation of 9 a under equilibrium, which is a previously -unreported feature of the haloform reaction. [45] A rate constant for the decay of acetophenone 1 a was experimentally determined and then locked into the model, enabling others to vary from it. Meanwhile, 1 H NMR analysis demonstrated that DBU and iodine form a strong adduct (see Supporting Information for full details), therefore these were represented as a single entity in the model.…”
mentioning
confidence: 99%
“…As trichloromethyl substrates are easy to prepare and commercially available, [10] their selective removal of chlorine atom(s) offers a direct and conventional approach to yield the corresponding dichloromethyl or monochloromethyl counterparts for the respective uses in the field of medicines, synthetic chemistry, and materials science. Current dechlorination strategies involve the use of Pd/C [11] or Pt/C, [12] PPh 3 /MeOH, [13] PPh 3 /H 2 O, [14] HBr/H 2 O, [15] RMgX/NH 4 Cl, [16] and various transition metals [17] . Selective mono‐ and didechlorination of trichloromethyl group were disclosed by the Peters group where reduction with tributyltin hydride in THF at 60 °C delivered dichloro product while reaction in refluxing toluene afforded monochloro product instead [18] .…”
Section: Introductionmentioning
confidence: 99%
“…传统的制备 α,α-二卤代酮的方法大致包括: (1) 芳 香酮的选择性卤化及芳炔、 芳烯和芳烷的氧化卤化反应, 该方法是利用 X 2 [13] 、NXS [14] 、I 2 /NaCI [15] 、1,3-二氯-5,5-二甲基海因(DCDMH) [16] 、H 2 O 2 /KBr [17] 、亚砜叶立德 [18] 、 ZnBr 2 /H 2 O [19] 、dioxane-dibromide [20] 、NaX/PhI(OAc) 2 [21] 、 48% HBr [22] 、K 2 S 2 O 8 [23] 和 TsNBr 2 [24] 等卤化试剂和氧化 剂来实现的; (2) α-多卤酮的脱卤反应, 该方法需要使用 10% Pt/C [25] 、PPh 3 /H 2 O [26] 、PPh 3 /MeOH [27] 、HBr/H 2 O [28] 、 苯硫酚 [29] 、RMgX/NH 4 Cl [30] 等还原性试剂来实现. 虽然 这些方法具有潜在的应用价值, 但是依然存在使用有 毒、危险或低原子经济性的卤化试剂, 或需要金属催化 剂和过量的强氧化剂, 反应选择性不易控制和条件苛刻 等问题.…”
unclassified